2023
DOI: 10.1111/jdv.19694
|View full text |Cite
|
Sign up to set email alerts
|

Clinically uninvolved but not healthy—The skin of patients with atopic dermatitis is primed for itch and inflammation

S. Moon,
O. Stasikowska‐Kanicka,
M. Wągrowska‐Danilewicz
et al.

Abstract: BackgroundAtopic dermatitis (AD) is a highly prevalent inflammatory skin disorder characterized by episodic exacerbations and remissions. Why the clinically healthy skin of AD patients becomes rapidly inflamed and very pruritic is poorly understood.ObjectiveTo investigate cowhage‐ and histamine‐induced itch and skin expression levels of their target receptors in lesional and non‐lesional skin of AD, compared to the skin of patients with psoriasis, chronic spontaneous urticaria (CSU) and healthy subjects.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
(173 reference statements)
0
3
0
Order By: Relevance
“…Additionally, in line with our findings in the high IFNG AD group, Th1/type 1-associated cytokines were identified in the adult- compared to the pediatric-onset AD cohort, in chronic compared to acute AD, and in intrinsic compared to extrinsic AD [ 38 , 39 , 40 , 41 ]. Furthermore, the PCA of the low IFNG AD group revealed less separation between the lesional and non-lesional transcriptome in comparison to the high IFNG group, which might be explained by a strong alteration of healthy skin in extrinsic AD [ 42 , 43 , 44 ]. Moreover, in the low IFNG AD group, a significant reduction was observed in lipid production (glycerolipid metabolic process), a hallmark of the impaired barrier characteristic of extrinsic AD [ 41 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in line with our findings in the high IFNG AD group, Th1/type 1-associated cytokines were identified in the adult- compared to the pediatric-onset AD cohort, in chronic compared to acute AD, and in intrinsic compared to extrinsic AD [ 38 , 39 , 40 , 41 ]. Furthermore, the PCA of the low IFNG AD group revealed less separation between the lesional and non-lesional transcriptome in comparison to the high IFNG group, which might be explained by a strong alteration of healthy skin in extrinsic AD [ 42 , 43 , 44 ]. Moreover, in the low IFNG AD group, a significant reduction was observed in lipid production (glycerolipid metabolic process), a hallmark of the impaired barrier characteristic of extrinsic AD [ 41 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though literature data are very limited, a proactive systemic treatment might modify disease progression, leading to pruritus alleviation, enhanced quality of life, less reliance on intensive topical treatments, improved psychological well-being, and secondary complications prevention. Besides, the chronic nature of AD and its association with atopic comorbidities, namely allergic rhinitis and asthma, further highlight the need to target the disease at its inception [ 6 ]. A recent meta-analysis regarding adolescent and adult AD under dupilumab demonstrated that the inhibition of IL-4/IL-13 hampered the development of new or the deterioration of established allergic conditions in a large AD clinical trial database in a highly atopic population [ 7 ].…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…Plaque psoriasis is an autoimmune disorder that primarily affects the skin, causing hyperproliferation of keratinocytes, manifesting as well-defined erythematous plaques covered with silvery-white scales [5]. PsA, on the other hand, is a type of spondyloarthritis often preceded and accompanied by psoriasis [6].…”
Section: Introductionmentioning
confidence: 99%